Analysis of Gender Representation in The Main Characters of The Film Barbie 2023: A Social Science Educational Perspective - Liza Dwi Eftiza Khairunniza; Sari Sri Handani; Dena Mustika; Yunita Haryani (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2024)
The Barbie 2023 film is an audiovisual work that provides an overview of popular culture and can influence gender perceptions in society. This research aims to explore gender representation among the main characters in the film Barbie 2023. Qualitative research methods with Roland Barthes' semiotic analysis techniques are used to find out the meaning construction of symbols and signs both verbal and nonverbal to explain gender representations in barbie films. The analysis displays gender stereotypes that influence the career choices, aspirations, and perceived abilities of the main characters. However, the film also depicts empowerment in which characters such as Barbie, Ken, and Midge challenge gender stereotypes, expand life options, and develop a social awareness of equality. The dynamics of relationships between characters also show changing views about gender. The correlation of this film with social studies education provides an opportunity to explore gender issues. This film is a learning material that stimulates critical thinking, reflection, and the development of students' social skills, such as empathy and cooperation, to fight for inclusive and just social change. The analysis of the Barbie 2023 film highlights the representation of the character's role in influencing gender perceptions, aspirations and the dynamics of social relationships. The film showcases the potential for overcoming gender stereotypes, promoting empowerment, and promoting gender equality as an integral part of social studies education to create an inclusive and just society for all individuals. Further studies could explore effective educational strategies to overcome gender stereotypes reflected in films, as well as their influence on students' mindsets in the context of gender equality.Keywords: Gender Stereotypes, Relationship Dynamics, Social Sciences Education.